Darstellung der Blutgefäße an der Hinterflosse des europäischen Seehundes (Phoca vitulina vitulina) und Beschreibung sowie Erprobung einer minimalinvasiven Blutentnahmelokalisation - Wehrmeister, Eva (Tierärztliche Hochschule, 2014)
Various localisations for veinpuncture for blood sampling at the hind flippers of harbour seal (Phoca vitulina vitulina) are described with varying success. Aim of this study was to re-evaluate the course of blood vessels at the hind flippers of harbour seal in comparison to grey seal. Based on this knowledge an appropriate localisation for veinpuncture, which can easily be included into medical training of seals should be tested. The anatomical preparation and depiction of blood vessels of the hind flipper of 22 harbour seals and five grey seals (Halichoerus grypus) were performed. In addition, the vessels of phocids/true seals were filled with different contrast media (Xenetix ® 350, barium sulfate and colored latex, as well as a mixture of barium sulfate, color and latex) followed by computer tomographic angiography (Philips Brilliance 64). Almost all arteries could be filled with contrast medium whereas only the main veins could be filled with contrast medium. The filled veins run at the plantar surface of the flippers and had mostly a parallel course to the bones. On the level of the tarsus and metatarsus, the plexus plantaris with its different effluxes and affluxions was represented. Veno-venous anastomoses were shown, whereas a difference between the venous course of harbour and grey seals could not be observed. The highest precision of bloodvessels-topography was reached by the computertomographic angiography. Vascular-like structures could be visualized by sonography in all phocids. A blood flow by Doppler sonography was only seen in 44.4% of the harbour seals and 71.4% in grey seals. Taking all results into account, localisation for blood sampling at the hind flipper is described at the plexus plantaris, which runs over the palpable Tuber calcanei. After description of this puncture site this method was assessed for practicability. In 58 trails a minimum volume of 0.5 ml was reached in 29.3%. The method is uncomplicated, easy to learn and can be used in trained animals without mechanical or chemical ...